2018
DOI: 10.1371/journal.pone.0206119
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of blood inflammatory markers for tuberculosis screening in people living with HIV

Abstract: BackgroundApproaches to screening for active tuberculosis (TB) among people living with HIV are inadequate, leading to missed diagnoses and poor implementation of preventive therapy.MethodsConsecutive HIV-infected adults hospitalized at Mulago Hospital (Kampala, Uganda) between June 2011 and July 2013 with a cough ≥ 2 weeks were enrolled. Patients underwent extensive evaluation for pulmonary TB. Concentrations of 43 cytokines/chemokines were measured at the same time point as C-reactive protein (CRP) in banked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…The plasma level of CRP, an activator of the classical complement pathway, increases during an inflammatory state and is widely used as a biomarker for pulmonary infections (35). Previous studies have shown that TB patients display higher CRP levels than healthy controls (36, 37), but in our study, no significant differences in serum CRP levels were observed between M. bovis-infected cattle and NC by iTRAQ analysis.…”
Section: Discussioncontrasting
confidence: 95%
“…The plasma level of CRP, an activator of the classical complement pathway, increases during an inflammatory state and is widely used as a biomarker for pulmonary infections (35). Previous studies have shown that TB patients display higher CRP levels than healthy controls (36, 37), but in our study, no significant differences in serum CRP levels were observed between M. bovis-infected cattle and NC by iTRAQ analysis.…”
Section: Discussioncontrasting
confidence: 95%
“…Other individual serum markers identified in our work included IL-6 and TGFα, both showing a good performance differentiating active TB from uninfected contacts. Our results agree with previous studies [12][13][14]16] that had reported diagnostic potential of IL-6, which indicates the robustness of this biomarker in different geographical settings. However, we have not found in the literature previous references of TGFα as a potential TB biomarker, which suggests that further research is required to investigate this new candidate.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we showed that accuracy of IP-10 as an individual biomarker can be improved when combined with IL-7 for discrimination between active TB and NoTBI contacts, or combined with BCA-1 to differentiate active TB and LTBI. Although previous studies have analysed an array of biomarkers in serum or plasma samples for TB diagnosis [10][11][12][13][14][15][16], none of them have proposed IL-7 or BCA-1 as potential biomarkers before. Our results suggest that they could not only be used in combination with IP-10, but they showed a good performance PLOS ONE differentiating active TB from both NoTBI and LTBI contacts when used individually, based on their respective AUCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunological and inflammatory environments of granulomas change due to the recirculation of immune cells and the release of cytokines that reach the periphery. Therefore, evaluations of cytokine/chemokine profiles in the blood are promising for the differentiation of infectious states in TB [68].…”
Section: Introductionmentioning
confidence: 99%